PENGARUH MOTIVASI DAN QUALITY OF WORKLIFE TERHADAP KINERJA PEGAWAI PT MEDCO E & P MALAKA ACEH TIMUR YANG DIMEDIASI OLEH EMPLOYEE ENGAGEMENT - Maulana, yuza; Lie, Darwin; Rostina, Cut Fitri (Mount Hope Economic Global Journal, 2025)
The purpose of the study is to analyze the influence of motivation on employee performance. This study aims to determine the extent to which employee motivation affects their performance levels. Motivation will be measured using indicators such as intrinsic and extrinsic needs. The test uses simple linear regression to measure the direct relationship between motivation (independent variable) and performance (dependent variable). Quantitative method. The results of the study Work motivation does not have a direct influence on employee performance with a P-Value of 0.462 indicating that partially work motivation is unable to improve employee performance in the long term. Quality of work life does not have a direct influence on employee performance with a P-Value of 0.523 indicating that partially the working environment conditions in the company are unable to improve employee performance even though the company has provided work facilities, health insurance, work safety guarantees, and training to employees. Work motivation has a direct influence on Employee Engagement with a P-Value of 0.042 indicating that the provision of appropriate facilities, awards, praise, and incentives can increase employee emotional involvement in the company. Work motivation has a direct influence on Employee Engagement with a P-Value of 0.042 indicating that the provision of appropriate facilities, awards, praise, and incentives can increase employee emotional involvement in the company.